Pengaruh Ulasan & Rating Online terhadap Impulsive Buying dengan Intervening Trust - Lutfiana, Retno Arum Angen (Innovative: Journal Of Social Science Research, 2024)
This study aims to evaluate the influence of online customer review and online customer rating on impulsive buying decisions through trust among Shopee users purchasing the moisturizer product "Skintific". The study population includes active Management students from Universitas PGRI Semarang, batch 2020-2023, with a total sample size of 346 respondents. The results indicate that online customer reviews have a significant impact and significance on trust in the Shopee marketplace among Management students at Universitas PGRI Semarang, batch 2020-2023. Additionally, online customer ratings also significantly influence trust. However, trust does not significantly influence impulsive buying decisions among this group. Nevertheless, online customer ratings are proven to significantly influence impulsive buying decisions.